The closed-mindedness that wasn’t: need for structure and expectancy-inconsistent information - Kemmelmeier, Markus (Frontiers in Psychology, 2015)
Social-cognitive researchers have typically assumed that individuals high in need for structure or need for closure tend to be closed-minded: they are motivated to resist or ignore information that is inconsistent with existing beliefs but instead they rely on category-based expectancies. The present paper argues that this conclusion is not necessarily warranted because previous studies did not allow individual differences in categorical processing to emerge and did not consider different distributions of category-relevant information. Using a person memory paradigm, Experiments 1 and 2 show that, when categorical processing is optional, high need-for-structure individuals are especially likely to use this type processing to reduce uncertainty, which results in superior recall for expectancy-inconsistent information. Experiment 2 demonstrates that such information is also more likely to be used in judgment making, leading to judgmental moderation among high need-for-structure individuals. Experiments 3 and 4 used a person memory paradigm which requires categorical processing regardless of levels of need for structure. Experiment 3 and 4 demonstrate that, whether expectancy-consistent or -inconsistent information is recalled better is a function of whether the majority of available information is compatible or incompatible with an initial category-based expectancy. Experiment 4 confirmed that the extent to which high need-for-structure individuals attend to different types of information varies with their distribution. The discussion highlights that task affordances have a critical influences on the consequences of categorical processing for memory and social judgment. Thus, high need for structure does not necessarily equate closed-mindedness.